Interaksi Genotipe x Lingkungan dan Stabilitas Karakter Agronomi Kedelai (Glycine max (L.) Merrill) - Sundari, Titik; Nugrahaeni, Novita (Perhimpunan Biologi Indonesia, 2016)
ABSTRACTResearch aimed to determine effect of genotype x environment interactions (GEI) on agronomic characters and yield stability of soybean genotypes were conducted at eight locations, namely Ngawi, Probolinggo, Banyuwangi, Jember, Malang, Sleman-Yogyakarta, Rembiga and Sesela-West Lombok. Materials used in the study were nine soybean genotypes consisting of six promising lines and three improved cultivars (Malabar, Wilis, and Ringgit). A randomized complete block design was used in each location, repeated four times. Observations were made on flowering days, maturity days, plant height, number of filled pods, seed weight per plant, 100 seed weight and seed yield. Results showed that the effect of GEI was significant on all of the observed agronomic characters. Maturity days, filled pods number, seed weight per plant, and seed yield were predominantly influenced by environmental factors, plant height and 100 seed weight were predominantly influenced by genetic factors, whereas flowering days was influenced by GEI. Genotype I/M-824-19 was stable with yield average lower compared to that of all genotypes and Agl/I-1114-8 was stable with yield average higher than the yield average of all genotypes. Wilis and M/IB-895-2 were classified as unstable, but gave yield average higher than the yield average of all genotypes.Keywords: adaptation, promising lines, soybean, stable